2001
DOI: 10.1002/glia.1074
|View full text |Cite
|
Sign up to set email alerts
|

The triakontatetraneuropeptide TTN increases [Ca2+]i in rat astrocytes through activation of peripheral‐type benzodiazepine receptors

Abstract: Astrocytes synthesize a series of regulatory peptides called endozepines, which act as endogenous ligands of benzodiazepine receptors. We have recently shown that one of these endozepines, the triakontatetraneuropeptide TTN, stimulates DNA synthesis in astroglial cells. The purpose of the present study was to determine the mechanism of action of TTN on cultured rat astrocytes. Binding of the peripheral-type benzodiazepine receptor ligand [3H]Ro5-4864 to intact astrocytes was displaced by TTN, whereas its C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Furthermore, when calcium was removed from extracellular medium, PK 11195 induced an inversed current, possibly due to the calcium efflux from the cytosol. The effect of exogenous and endogenous PBR ligands on activation of L-type Ca 2ϩ channels has been previously reported (14,59). It was also shown that PBR ligands provoke chloride efflux related to calcium influx via L-type Ca 2ϩ channels in the rat astrocytes (14).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, when calcium was removed from extracellular medium, PK 11195 induced an inversed current, possibly due to the calcium efflux from the cytosol. The effect of exogenous and endogenous PBR ligands on activation of L-type Ca 2ϩ channels has been previously reported (14,59). It was also shown that PBR ligands provoke chloride efflux related to calcium influx via L-type Ca 2ϩ channels in the rat astrocytes (14).…”
Section: Discussionmentioning
confidence: 93%
“…The effect of exogenous and endogenous PBR ligands on activation of L-type Ca 2ϩ channels has been previously reported (14,59). It was also shown that PBR ligands provoke chloride efflux related to calcium influx via L-type Ca 2ϩ channels in the rat astrocytes (14). On the other hand, it has been indicated that DBI elicits intracellular Ca 2ϩ oscillations in STC-1 cells inhibited by L-type Ca 2ϩ channel blockers (59).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In mammals ACBP is processed to form diazepam binding inhibitor, which modulates the GABA A receptor in the brain and affects various peripheral organs (17)(18)(19). In the brain, ACBP is processed to an anionic peptide of 36 aa (triakontatetraneuropeptide, TTN) and its C-terminal 20-aa fragment (ODN) (Fig.…”
Section: Disruption Of Acba Affects Sporulation and Sdf-2 Productionmentioning
confidence: 99%
“…DBI and ODN act as inverse agonists of central-type benzodiazepine receptors (CBR) associated with the GABA A receptor complex (Guidotti et al, 1983;Tonon et al, 1989;Bormann, 1991;Louiset et al, 1993). TTN acts preferentially through peripheral-type benzodiazepine receptors (PBR) located either at the outer mitochondrial membrane or at the plasma membrane level Berkovich et al, 1990;Gandolfo et al, 2001). Finally, ODN can also activate a metabotropic receptor positively coupled to phospholipase C through a pertussis toxin-sensitive G-protein (Patte et al, 1995;Gandolfo et al, 1997).…”
Section: Introductionmentioning
confidence: 99%